Identification of Root-Associated Bacteria That Influence Plant Physiology, Increase Seed Germination, or Promote Growth of the Christmas Tree Species Abies nordmanniana - Garcia-Lemos, Adriana M.; Großkinsky, Dominik K.; Saleem Akhtar, Saqib; Nicolaisen, Mette Haubjerg; Roitsch, Thomas; Nybroe, Ole; Veierskov, Bjarke (Frontiers in Microbiology, 2020)
Abies nordmanniana is used for Christmas tree production but poor seed germination and slow growth represent challenges for the growers. We addressed the plant growth promoting potential of root-associated bacteria isolated from A. nordmanniana. Laboratory screenings of a bacterial strain collection yielded several Bacillus and Paenibacillus strains that improved seed germination and produced indole-3-acetic acid. The impact of three of these strains on seed germination, plant growth and growth-related physiological parameters was then determined in greenhouse and field trials after seed inoculation, and their persistence was assessed by 16S rRNA gene-targeted bacterial community analysis. Two strains showed distinct and significant effects. Bacillus sp. s50 enhanced seed germination in the greenhouse but did not promote shoot or root growth. In accordance, this strain did not increase the level of soluble hexoses needed for plant growth but increased the level of storage carbohydrates. Moreover, strain s50 increased glutathione reductase and glutathione-S-transferase activities in the plant, which may indicate induction of systemic resistance during the early phase of plant development, as the strain showed poor persistence in the root samples (rhizosphere soil plus root tissue). Paenibacillus sp. s37 increased plant root growth, especially by inducing secondary root formation, under in greenhouse conditions, where it showed high persistence in the root samples. Under these conditions, it further it increased the level of soluble carbohydrates in shoots, and the levels of starch and non-structural carbohydrates in roots, stem and shoots. Moreover, it increased the chlorophyll level in the field trial. These findings indicate that this strain improves plant growth and vigor through effects on photosynthesis and plant carbohydrate reservoirs. The current results show that the two strains s37 and s50 could be considered for growth promotion programs of A. nordmanniana in greenhouse nurseries, and even under field conditions.